Tissue-engineered acellular small diameter long-bypass grafts with neointima-inducing activity. (July 2015) - Mahara, Atsushi; Somekawa, Shota; Kobayashi, Naoki; Hirano, Yoshiaki; Kimura, Yoshiharu; Fujisato, Toshiya; Yamaoka, Tetsuji
Abstract: Researchers have attempted to develop efficient antithrombogenic surfaces, and yet small-caliber artificial vascular grafts are still unavailable. Here, we demonstrate the excellent patency of tissue-engineered small-caliber long-bypass grafts measuring 20–30 cm in length and having a 2-mm inner diameter. The inner surface of an acellular ostrich carotid artery was modified with a novel heterobifunctional peptide composed of a collagen-binding region and the integrin α4β1 ligand, REDV. Six grafts were transplanted in the femoral–femoral artery crossover bypass method. Animals were observed for 20 days and received no anticoagulant medication. No thrombogenesis was observed on the luminal surface and five cases were patent. In contrast, all unmodified grafts became occluded, and severe thrombosis was observed. The vascular grafts reported here are the first successful demonstrations of short-term patency at clinically applicable sizes.